2022
DOI: 10.3390/vaccines10060871
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Reactogenicity of mRNA BNT162b2 COVID-19 Vaccine among Thai Adolescents with Chronic Diseases

Abstract: Adolescents with underlying diseases are at risk of severe COVID-19. The immune response of BNT162b2 may be poor among immunocompromised adolescents. We aim to describe immunogenicity of mRNA BNT162b2 among adolescents who are immunocompromised or have chronic diseases. We recruited adolescents 12–18 years of age; group A impaired-immunity (post-transplantation, cancer, on immunosuppressive drugs) and group B chronic diseases. A two-dose regimen of BNT162b2 was given. Immunogenicity was determined by surrogate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
6
7
0
Order By: Relevance
“…The higher frequency of adverse reactions in those with allergic diseases was consistent with previous reports on adults [39]. It has been suggested that individuals with allergic diseases, such as asthma, who are potentially susceptible to COVID-19 [8; [25][26][27][28][29], may experience more adverse reactions after BNT162b2 vaccination. Therefore, to ensure that children with allergic diseases, receive the vaccine safely, further information regarding adverse reactions and long-term effects of BNT162b2 vaccination needs to be collected.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The higher frequency of adverse reactions in those with allergic diseases was consistent with previous reports on adults [39]. It has been suggested that individuals with allergic diseases, such as asthma, who are potentially susceptible to COVID-19 [8; [25][26][27][28][29], may experience more adverse reactions after BNT162b2 vaccination. Therefore, to ensure that children with allergic diseases, receive the vaccine safely, further information regarding adverse reactions and long-term effects of BNT162b2 vaccination needs to be collected.…”
Section: Discussionsupporting
confidence: 87%
“…Adverse reactions in this population were generally non-serious, more common after second vaccination, and substantially less common than those observed among individuals aged 12-15 years [22][23][24]. Children with underlying comorbidities are at risk of severe COVID-19 [8; [25][26][27][28][29]; however, long-term data on the adverse reactions after BNT162b2 vaccination in these patients are limited. Fukushima Prefecture, Japan began administering BNT162b2 as two doses (10 µg, 0.2 mL each), three weeks apart to individuals aged 5-11 years on March 9, 2022.…”
Section: Introductionmentioning
confidence: 99%
“…The higher frequency of adverse reactions in those with allergic diseases was consistent with previous reports on adults [ 40 ]. It has been suggested that individuals with allergic diseases, such as asthma, who are potentially susceptible to COVID-19 [ 8 , 25 29 ], may experience more adverse reactions after BNT162b2 vaccination. Therefore, to ensure that children with allergic diseases receive the vaccine safely, further information regarding adverse reactions and long-term effects of BNT162b2 vaccination needs to be collected.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, their underlying immune deficiency or immunosuppressive treatment might impair their ability to respond to the vaccine and develop protective immunity, characterized by generating anti-SARS-CoV-2 antibodies and cellular immune responses ( 5 , 13 ). Some evidence exists regarding the effects of vaccination outcomes in adult immunocompromised individuals ( 18 ), while the protective immunity elicited by vaccines in immunocompromised children was mainly focused on the humoral response ( 19 , 20 ). In one study, it was shown that adolescents who are immunocompromised (post-transplantation, cancer, or due to immunosuppressive drugs) displayed impaired in vitro neutralization capacity as measured by competition with ACE2, and total IgG against RBD, in comparison to adolescents who have chronic diseases, such as HIV.…”
Section: Introductionmentioning
confidence: 99%